105k views
1 vote
Factor Sin^2X + 7 Cos X + 7

User Suave
by
5.1k points

1 Answer

5 votes

Answer:


\begin{equation*}% \mbox{\large\( % - \left(\cos \left(x\right)+1\right)\left(\cos \left(x\right)-8\right)\)} %\end{equation*}

Explanation:

sin²(x) = 1 - cos²(x)

So the expression sin²(x) + 7cosx +7 becomes

1 - cos²(x) + 7cos(x) + 7

Group like terms


\begin{equation*}% \mbox{\large\( %=-\cos ^2\left(x\right)+7\cos \left(x\right)+1+7 %\)} %\end{equation*}


\begin{equation*}% \mbox{\large\( %=-\cos ^2\left(x\right)+7\cos \left(x\right)+8 %\)} %\end{equation*}
\begin{equation*}% \mbox{\large\( %=-\cos ^2\left(x\right)+7\cos \left(x\right)+1+7 %\)} %\end{equation*}
\begin{equation*}% \mbox{\large\( %=7\cos \left(x\right)-\cos ^2\left(x\right)+8\)} %\end{equation}


\begin{equation*}% \mbox{\large\( %=-\left(\cos ^2\left(x\right)-7\cos \left(x\right)-8\right)\)} %\end{equation}


Let's deal with the expression in parenthesis

\begin{equation}% \mbox{\large\( %=\cos ^2\left(x\right)-7\cos \left(x\right)-8\)} %\end{equation}
\begin{equation*}% \mbox{\large\( %=\cos ^2\left(x\right)-7\cos \left(x\right)-8)} %\end{equation}


\begin{equation*}% \mbox{\large\( %\cos^2(x) - 7\cos(x)-8\)} %\end{equation*}\\\\

This is of the form
\begin{equation*}% \mbox{\large\( %ax^2 + bx + c\)} %\end{equation*}

with a = 1, b = -7 and c = -8

To factor this find two values u and v such that


\begin{equation*}% \mbox{\large\( %u\cdot v = -8, v + v = -7\)} %\end{equation*}

If we choose u = 1 and v = -8 we can satisfy the above relationship since
u · v = 1 (-8) = -8 and u + v = 1 +(-8) = -7


\displaysize {\textrm{Group\:into\:}\left(ax^2+ux\right)+\left(vx+c\right)}

\begin{equation*}% \mbox{\large\( %\left(\cos ^2\left(x\right)+\cos \left(x\right)\right)+\left(-8\cos \left(x\right)-8\right)\)} %\end{equation*}


\textrm{Factor\:out}\:\cos \left(x\right)\:\mathrm{from}\:\cos ^2\left(x\right)+\cos \left(x\right)


\begin{equation*}% \mbox{\large\( %=\cos \left(x\right)\left(\cos \left(x\right)+1\right)\)} %\end{equation*}


\textrm{Factor\:out}\:-8\:\mathrm{from}\:-8\cos \left(x\right)-8:


=-8\left(\cos \left(x\right)+1\right)

So

\begin{equation*}% \mbox{\large\( %\left(\cos ^2\left(x\right)+\cos \left(x\right)\right)+\left(-8\cos \left(x\right)-8\right)\)} %\end{equation*}

=
\begin{equation*}% \mbox{\large\( %\cos \left(x\right)\left(\cos \left(x\right)+1\right)-8\left(\cos \left(x\right)+1\right)\)} %\end{equation*}


\textrm{Factor\:out\:common\:term\:}\cos \left(x\right)+1

\begin{equation*}% \mbox{\large\( %=\left(\cos \left(x\right)+1\right)\left(\cos \left(x\right)-8\right)\)} %\end{equation*}

Since this was the term in the parenthesis with a leading negative sign, add the negative sign to get


\begin{equation*}% \mbox{\large\( %1-\cos ^2\left(x\right)+7\cos \left(x\right)+7\)} %\end{equation*}
\begin{equation*}% \mbox{\large\( %= - \left(\cos \left(x\right)+1\right)\left(\cos \left(x\right)-8\right)\)} %\end{equation*}
\begin{equation*}% \mbox{\large\( %= - \left(\cos \left(x\right)+1\right)\left(\cos \left(x\right)-8\right)\)} %\end{equation*}\\

Answer:
\begin{equation*}% \mbox{\large\( % - \left(\cos \left(x\right)+1\right)\left(\cos \left(x\right)-8\right)\)} %\end{equation*}

User Kevin Pastor
by
5.6k points